Humanistic education Management: A comparative Analysis of Indonesia’s KBC and Singapore’s CCE - Ade Sonnie Aglesia; Lukman Asha; Fakhruddin Fakhruddin (UIN Siber Syekh Nurjati Cirebon, 2025)
This study examines the humanistic education management models implemented through Indonesia’s Love-Based Curriculum (KBC) and Singapore’s Character and Citizenship Education (CCE). Using a comparative analysis approach, the research explores the philosophical foundations, implementation patterns, and evaluation mechanisms of both curricula. The findings reveal that KBC emphasizes spiritual–religious values and the five forms of love as its core principles, resulting in a flexible and contextual curriculum oriented toward character formation through daily experiences. However, KBC still faces limitations in evaluation due to the absence of standardized assessment instruments. In contrast, Singapore’s CCE is supported by a comprehensive national framework, clear competency indicators, and structured assessments, enabling consistent implementation across schools. Despite their differences, both models share a common goal of fostering holistic learners. The study concludes that integrating Indonesia’s value-deepening approach with Singapore’s systematic evaluation model can enrich the development of humanistic education management in the future.